Abnormal Circulating Leukaemia-like Megakaryoblasts In The Placenta Of A Stillborn: Congenital Leukaemia (CL) Transient Abnormal Myelopoiesis (TAM) - Nur Syahrina Rahim; Shahril Fikri Zul Hasnan Najib; Khairul Anuar Zainun; Norashikin Abdul Fuad; Abdul Rahman Hayati (Academy of Medicine of Malaysia, 2024)
Volume : 40 Issue : 2